ФАЗА РАСПУСКАНИЯ ВЕГЕТАТИВНЫХ ПОЧЕК У СОРТОВ ЯБЛОНИ В ЦЕНТРАЛЬНОМ КАЗАХСТАНЕ (Experimental biology, 2009)
The results on the study of biological characters of the beginning vegetation of apple cultivars in an experimental plot in the Zhezkazgan Botanical Garden are stated in the article. Three apple cultivars groups are chosen with different time of the beginning of vegetation.
Keywords: vegetation